2017
DOI: 10.1002/anie.201706297
|View full text |Cite
|
Sign up to set email alerts
|

Highly Bent 1,3‐Digerma‐2‐silaallene

Abstract: A 1,3-digerma-2-silacyclopenta-1,2-diene, that is, a 1,3-digerma-2-silaallene incorporated into a five-membered ring system, was synthesized and obtained as a stable orange solid. Owing to incorporation into a cyclic framework, the 1,3-digerma-2-silaallene moiety is highly bent, exhibiting a Si character for the central silicon moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…The subsequent treatment of 19 with four molar equivalents of KC 8 in benzene at ambient temperature afforded orange crystals of 1,3‐digerma‐2‐silaallene 20 in 57 % yield. The 29 Si NMR spectrum of a [D 8 ]THF solution of 20 revealed a signal at δ 29 Si=−16.5 ppm for the central silicon atom, which is strongly upfield shifted compared to that of 1,3‐digermasilaallene 7 (δ 29 Si=236.6 ppm) and that calculated for the less hindered 1,1′,3,3′‐tetramethyl‐digermasilaallene (δ 29 Si=129.4 ppm), which indicates that the Si(0) character should be a consequence of the rigid cyclic structure . The unexpectedly upfield‐shifted 29 Si NMR shift is probably due to the σ‐donating properties of the germylene moieties and the acute Ge‐Si‐Ge angle caused as a result of rigid cyclic skeleton.…”
Section: Homoleptic Tetrylonesmentioning
confidence: 97%
See 2 more Smart Citations
“…The subsequent treatment of 19 with four molar equivalents of KC 8 in benzene at ambient temperature afforded orange crystals of 1,3‐digerma‐2‐silaallene 20 in 57 % yield. The 29 Si NMR spectrum of a [D 8 ]THF solution of 20 revealed a signal at δ 29 Si=−16.5 ppm for the central silicon atom, which is strongly upfield shifted compared to that of 1,3‐digermasilaallene 7 (δ 29 Si=236.6 ppm) and that calculated for the less hindered 1,1′,3,3′‐tetramethyl‐digermasilaallene (δ 29 Si=129.4 ppm), which indicates that the Si(0) character should be a consequence of the rigid cyclic structure . The unexpectedly upfield‐shifted 29 Si NMR shift is probably due to the σ‐donating properties of the germylene moieties and the acute Ge‐Si‐Ge angle caused as a result of rigid cyclic skeleton.…”
Section: Homoleptic Tetrylonesmentioning
confidence: 97%
“…Sasamori and Tokitoh have recently devised a molecular design to reduce the central E=E=E angle in trimetallallenes by incorporating the E=E=E moiety into a rigid five‐membered ring skeleton, which enhances the ylidone E(0) character. Specifically, heating 1,2‐Bbt 2 ‐1,2‐digermacyclobutene 18 in neat SiCl 4 for 12 h to 55 °C resulted in the formation of 1,1,2,5‐tetrachloro‐2,5‐digerma‐1‐sila‐cyclopentane 19 in quantitative yield as colorless crystals (Scheme ).…”
Section: Homoleptic Tetrylonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Si(II) or Ge(II) species should be an important building block for creating such halogenated oligosilanes/germanes because silylenes (divalent Si(II) species) or germylenes (divalent Ge(II) species) have been known to undergo ready Si-Cl insertion reactions, i.e., Si-Cl activation reactions [8][9][10][11]. For example, Iwamoto and Kira reported the facile Si-Cl insertion of the isolable dialkylmetallylenes towards SiCl 4 under mild conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was found that the stable 1,2-digermacyclobutadiene 1 (1,2-Tbb 2 -3,4-Ph 2 -digermacyclobutadiene, Tbb = 2,6-[CH(SiMe 3 ) 2 ] 2 -4-t-Bu-C 6 H 2 , Scheme 2) [24] with SiCl 4 afforded the corresponding 1,3-digerma-2-sila-cyclopent-4-ene derivative, the cyclic >Ge(Cl)-SiCl 2 -Ge(Cl)< compound. 1,2-Digermacyclobut-1-ene derivative was reacted with SiCl 4 to give the double-Si-Cl-insertion product, and the following reduction reaction gave the corresponding > Ge = Si = Ge < species [11]. Although 1 could undergo facile double Si-Cl activation toward SiCl 4 , neither double Ge-Cl nor C-Cl activation could occur in the reaction of 1 with GeCl 4 /CCl 4 .…”
Section: Introductionmentioning
confidence: 99%